Prenylated phenylpropanoids with unprecedented skeletons from Illicium burmanicum. Issue 18 (9th February 2017) - Tian, Xinhui; Guo, Xin; Zhuo, Zhiguo; Zeng, Rentao; Fang, Xin; Xu, Xike; Li, Huiliang; Shen, Yunheng; Zhang, Weidong
Abstract : Two hetero adducts (1 and2 ) which showed cytotoxic on A549 and HCT116 cells at 6.40–7.76 μM were isolated from Illicium burmanicum . Abstract : A phytochemical investigation on the branches and leaves of Illicium burmanicum led to the isolation of two unique allo-thujane-phenylpropane and lavandulane-phenylpropane hetero-adducts (1 and2 ), two new prenylated phenylpropanoids (3 and4 ), and one new neolignan (5 ). Their structures were established by comprehensive NMR and CD spectroscopic analysis. Burmaniols A (1 ) and B (2 ) showed appreciable cytotoxicity against A549 and HCT116 cells with IC50 values of 6.40–7.76 μM.